Aquisição variável de sequências triconsonantais Ct/d]σC por falantes campinenses de inglês como L2 - Reis, Felipe Santos dos (2019)
This work aims to investigate the acquisition of an English variable phonological pattern by L2 learners from the city of Campina Grande in the state of Paraíba, Brazil. More specifically, the variation that motivated the study described here involves consonant sequences where the coronal plosives are flanked by heterosyllabic consonants, since L1 English speakers tend to delete /t,d/ in Ct/d]σC, which is considered a marked structure that may cause more difficulties than simplex codas or sequences with only two members, for example. Thus, we propose the hypothesis that Brazilian learners of L2 English, especially in the initial stages of acquisition, would resort more often to the use of a vocalic epenthesis, similarly to what occurs in their native language in the context of words such as “ad[i]vogado” e “ad[i]mirar”. The use of this strategy is caused by the restriction that determines the well-formedness of coda in Brazilian Portuguese, which does not permit stops in syllable-final position: when an unlicensed segment, like plosives, occurs in such a position in the underlying representation, the stray consonant is syllabified as the onset of an empty nucleus inserted at its right, filled with the additional high front vowel [i] post-lexically (COLLISCHONN, 2004). Thus, considering the variable deletion rule of (t,d) between heterosyllabic consonants in English as an L1, as well as the lack of consonant sequences containing three members in PB, such as Ct/d]σC, the purpose of this sociolinguistic study (LABOV, 1972/2008) is to describe and explain the variation in the interlanguage of English as an L2 learners from the state of Paraíba, with respect to the production of this phonological pattern. More specifically, we aimed to analyze the interlanguage of L2 learners from the city of Campina Grande (PB) in order to achieve the following specific objectives: (1) to detect the variants present in the interlanguage of L2 learners of English in the process of acquiring sequences of the type Ct/d]σC; (2) to describe the developmental stages in the process of second-language acquisition regarding the aforementioned structure; and, finally, (3) to reflect on the effects of each internal and external factor on the conditioning of the detected variants. To that end, 24 subjects were asked to read aloud a list of 43 target words embedded in 160 carrier sentences containing bimorphemic words in English with consonant sequences where the coronal plosives occur between two heterosyllabic consonants. The remaining 117 phrases were used as distractors, to prevent informants from becoming aware of the structure in advance. Thus, 1,071 tokens were audiorecorded and submitted to a multivariate analysis by means of two statistical tools, namely GoldVarb X (SANKOFF; TAGLIAMONTE; SMITH, 2005) and Rbrul (JOHNSON, 2015), as an attempt to compare results and thereby provide a more detailed and enriched picture of phenomenon. Two other instruments, one in Portuguese and another one in English, were applied to 12 of the 24 individuals who participated in the first round of data collection (i.e., reading carrier sentences in English). 960 tokens of codas containing plosive sounds in the underlying representations of vernacular words and anglicisms used in BP were captured and quantitatively analyzed by GoldVarb X, which helped us explain the behavior of the investigated group of learners. The outputs produced by the population show that the adjustments in the sequences Ct/d]σC are conditioned by the sonority, following universal principles of syllable structure, such as the Sonority Cycle Principle, proposed by Clements (1990), and also by the apparent lack of familiarity with the English phonological system, as in the case of learners at basic levels of L2 proficiency. We infer that the sociolinguistic pattern cannot be explained solely on the basis of the language itself: it is crucial to take into account the dynamic and inseparable interrelations between speaker, language and society.